LINGUISTIC ARAB DI ZAMAN MODERAN : PERKEMBANGAN, TANTANGAN DAN PENERAPANNYA DALAM KONTEKS GLOBALISASI - HAFIZ, KHAIRUL; WAHYUDIN, DEDY; SURIANI, ERMA (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2024)
The title of this research, "Arabic Linguistics in the Modern Era: Development, Challenges and Applications in the Context of Globalization" aims to explore the dynamics of the development of the Arabic language in the context of changing times that are increasingly interconnected globally. . Arabic as a language that has an important role in the world of religion, culture and politics faces various challenges in the modern era, including the impact of globalization, technological advances and global linguistic developments. This research explores how Arabic adapts to global communication needs, as well as its role in the world of academia, media, and professional sectors are evolving with modernization. Apart from that, this article also discusses the challenges faced by Arabic speakers, such as changes in language use, the phenomenon of linguistic diglossia, and the difficulty of maintaining the originality of the Arabic language amidst the dominance of foreign languages. This research is expected to provide insight into the importance of the Arabic language and its application in global society. currently, in addition to contributing to linguistic studies. ABSTRAKJudul penelitian ini, “Linguistik Arab di Era Modern: Perkembangan, Tantangan, dan Penerapan dalam Konteks Globalisasi” bertujuan untuk mengeksplorasi dinamika perkembangan bahasa Arab dalam konteks perubahan zaman yang semakin saling berhubungan secara global. . Bahasa Arab sebagai bahasa yang mempunyai peranan penting dalam dunia agama, budaya dan politik menghadapi berbagai tantangan di era modern, antara lain dampak globalisasi, kemajuan teknologi dan perkembangan linguistik global.Penelitian ini mengeksplorasi bagaimana bahasa Arab beradaptasi dengan kebutuhan komunikasi global, serta bagaimana perannya dalam dunia akademis, media, dan sektor profesional berkembang seiring modernisasi. Selain itu, artikel ini juga membahas tantangan yang dihadapi penutur bahasa Arab, seperti perubahan penggunaan bahasa, fenomena diglosia linguistik, dan sulitnya mempertahankan orisinalitas bahasa Arab di tengah dominasi bahasa asing.Penelitian ini diharapkan dapat memberikan wawasan mengenai pentingnya bahasa Arab dan penerapannya dalam masyarakat global saat ini, selain memberikan kontribusi terhadap kajian linguistik.